1999
DOI: 10.1093/brain/122.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Coherent cortical and muscle discharge in cortical myoclonus

Abstract: There is increasing evidence in man that the cortical drive to motor neurons is rhythmic. This oscillatory drive may be exaggerated in patients with cortical myoclonus. Spectral analysis of surface bipolar EEG and EMG activity was performed in eight such patients. Only three cases had evidence of giant cortical evoked potentials or a cortical correlate on back-averaging at the time of study. In six subjects, significant coherence between contralateral and vertex EEG and EMG was observed in ranges similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 32 publications
6
85
1
Order By: Relevance
“…Moreover, the sensitivity and specificity of the neurophysiological methods used are unknown (except for SSEP as prognosticator in PAE). On the other hand, JLBA and coherence analysis have proven their role in clinical practice in evaluating anatomical origin of myoclonus and can therefore be seen as a reliable marker 11, 18, 20, 21, 22, 31. Indeed, the agreement between JLBA and coherence analysis turned out to be substantial: 17/19 patients had identical findings.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, the sensitivity and specificity of the neurophysiological methods used are unknown (except for SSEP as prognosticator in PAE). On the other hand, JLBA and coherence analysis have proven their role in clinical practice in evaluating anatomical origin of myoclonus and can therefore be seen as a reliable marker 11, 18, 20, 21, 22, 31. Indeed, the agreement between JLBA and coherence analysis turned out to be substantial: 17/19 patients had identical findings.…”
Section: Discussionmentioning
confidence: 95%
“…To classify the anatomical origin of PHM, five different neurophysiological methods were used, namely: (1) visual inspection of EEG, (2) EMG burst‐duration, (3) muscle recruitment order, (4) JLBA, and (5) coherence analysis 6, 9, 10, 11, 18, 19, 20, 21, 22. Cortical PHM was presumed if (1) an EEG spike prior PHM was visible on EEG, (2) a mean burst duration <75 msec was present (10 randomly assessed jerks), (3) a cranio‐caudal muscle recruitment order or only single myoclonic jerk(s) were present, (4) JLBA was positive, or (5) reliable corticomuscular coherence was present.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramuscular coherence is a measure of the common input to different parts of the same muscle and is applied as a measure of the corticospinal drive (Grosse et al, 2003(Grosse et al, , 2002Brown et al, 1999). We found that the reliability and agreement of intramuscular coherence variables depends on signal processing settings (EMG high-pass filtering and rectification) and experimental condition (walking speed).…”
Section: Discussionmentioning
confidence: 89%
“…Coherence derived from a pair of EMG signals, EMG-EMG coherence, quantifies the common oscillatory drive to a pair of muscles (intermuscular coherence) or to two parts of the same muscle (intramuscular coherence). EMG-EMG coherence in the beta (15−35Hz) bands is considered to reflect the common corticospinal drive from the primary motor cortex to the muscles (Hansen et al, 2001;Grosse et al, 2003;Halliday et al, 2003;Grosse et al, 2002;Petersen et al, 2010;Brown et al, 1999) whereas also spinal circuitries could potentially contribute (Norton et al, 2004(Norton et al, , 2003. EMG-EMG coherence is an attractive approach to assess this common drive since it is easy to measure, requiring only the recording of EMG signals without the need to perturb or stimulate the system (Bo Nielsen, 2002;Barthélemy et al, 2010;Hansen et al, 2005;Norton, 2008).…”
Section: Introductionmentioning
confidence: 99%